Observable score for bleeding after colorectal endoscopic mucosal resection - Hayato Nakazawa; Kenichiro Okimoto; Tomoaki Matsumura; Masayuki Yokoyama; Tsubasa Ishikawa; Yoshihiro Fukuda; Yoshio Kitsukawa; Akane Kurosugi; Michiko Sonoda; Tatsuya Kaneko; Yuki Ohta; Takashi Taida; et al. (Therapeutic Advances in Gastroenterology)
Background: There is insufficient evidence regarding the management of hematochezia after colorectal endoscopic mucosal resection (EMR) without endoscopic hemostasis. Objectives: The aim of this study was to develop an observable score for hematochezia after colorectal EMR. Design: Retrospective study. Methods: This retrospective study included three hospitals in Japan. During the study period, colorectal EMR was performed in 3989 patients (11,414 lesions). Post-EMR hematochezia (delayed bleeding (DB)) was observed in 169 patients (512 lesions). Of these, 47 patients (150 lesions) were classified into the Hemostasis Group, comprising those who underwent endoscopic hemostasis. The remaining 122 (362 lesions) were classified into the non-hemostasis group, comprising those who underwent endoscopy without hemostasis, received preventive hemostasis, and did not undergo emergency endoscopy. Weighted points were assigned to predict observable cases following colorectal EMR through multivariate logistic regression analysis, enabling the development of a predictive model. Results: The prediction model comprised three variables (male gender, American Society of Anesthesiologists Physical Status 3, direct oral anticoagulant). According to the definition, the total score was categorized as lowly observable (2 or 3 points) and highly observable (0 or 1 points) for DB after colorectal EMR. As a result, the rates of observable cases for each risk category were 45.7% and 81.8%, respectively. The model showed good discrimination ability from the c-statistic (95% CI) of 0.71 (0.63–0.79). Conclusion: Although further prospective studies are necessary to validate the utility of the score, it may be useful in clinical practice.